Retaining women students in science involves more than course selection. - Donaldson, E. L.; Dixon, E. A. (Canadian Journal of Higher Education, 1995)
Difficulties in retaining women students in undergraduate science courses are well known, but reasons for the attrition are less well understood. Data from a survey of first-year chemistry students suggests that gender differences with regard to pre-entry attributes and the transition to the university, the on- campus experience, perceived competencies in academic skills and science literacy, and undergraduate transitions to work may contribute to decisions to leave science, but not necessarily to leave the university. In one university, short-term intervention strategies such as curricula changes, the addition of female faculty role models, the introduction of promotional activities, and the formation of peer support groups are increasing retention. Follow-up data from Phase Two of this study should provide other indicators, but differences in course selection between young women and men enrolled in university appear to be influenced by their values, thus contributing to differing career choices.